Peran Dimensi Productive Parenting Pattern terhadap Pembentukan Grit pada Mahasiswa - Jostein Adams; Ni Luh Ayu Vivekananda (Universitas Negeri Makassar, 2023)
College students need to have the consistency to accomplish their major of studies in which they have passion and show persistence until they graduate to start working. The purpose of this study is to analyze the influence of each Productive Parenting Pattern dimensions as one of the external factor on developing Grit from college students.This study employed a quatitative approach with causal design on 466 college students using snowball sampling. Each participant completed the Productive Parenting Pattern questionnaire based on Alvy’s theory and the Grit questionnaire based on Angela Duckworth’s theory. The data were analyzed using simple linear regression. The results indicated that the dimensions of productive parenting pattern significantly influence the development of grit in college students (high parental acceptance and warmth r2=.068, p=.000; moderate to high restrictiveness r2=.075, p=.000; insistence on mature behavior r2=.074, p=.000; high responsiveness r2=.057, p=.000; high positive involvement r2=.066, p=.000). The resuts indicates that productive parenting pattern, as a positive parenting style, plays a significant role in shaping college students' passion and perseverance in achieving their long-term goals.